Answer:
2 e⁻ + 4 H⁺(aq) + MnO₂(s) → Mn²⁺(aq) + 2 H₂O(l)
Step-by-step explanation:
Let's write the half-reaction for the reduction of solid manganese dioxide MnO₂ to manganese ion Mn²⁺ in acidic aqueous solution.
MnO₂(s) → Mn²⁺(aq)
To balance the oxygen atoms, we will add 2 moles of water on the right side. To compensate for the hydrogen atoms added, we will add 4 hydrogen ions on the left side.
4 H⁺(aq) + MnO₂(s) → Mn²⁺(aq) + 2 H₂O(l)
Finally, we will balance the charges by adding 2 electrons on the left side.
2 e⁻ + 4 H⁺(aq) + MnO₂(s) → Mn²⁺(aq) + 2 H₂O(l)